The Effect of Taxable Person Compliance and Tax Collection on Value Added Tax Revenue : (Study at The Primary Tax Service Office in The City of Bandung) - Karina Nurmaya; Lissa Rosdiana Noer (Publikasi Indonesia, 2025)
The development of the amount of tax arrears from time to time shows an increasing amount and has not been balanced with its disbursement activities, for that it is necessary to carry out tax collection actions based on applicable laws and regulations. This study aims to determine whether there is an effect of taxable person compliance and tax collection on value added tax revenue at the primary tax service office in the city of Bandung. The research method used is quantitative descriptive. Determination of the sample using total sampling with a total of 4 primary tax service offices. The test analysis was carried out by panel data linear regression test using eviews, hypothesis testing and determination coefficient testing. The results of the study indicate that taxable person compliance has an effect on value added tax revenue and tax collection has an effect on value added tax revenue at the primary tax service office in the city of Bandung.